2021
DOI: 10.1007/s11356-021-16078-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of potential benefits of traffic and urban mobility reductions during COVID-19 lockdowns: dose-response calculations for material corrosions on built cultural heritage

Abstract: Air pollution, particularly in urban areas, puts human health in danger and has adverse impacts on the built environment. It can accelerate the natural corrosion rate of cultural heritages and monuments, leading to premature aging and lowering their aesthetic value. Globally, at the beginning of 2020, to tackle the spread of novel COVID-19, the lockdown was enforced in the most hard-hit countries. Therefore, this study assesses, as a first time, the plausible benefits of traffic and urban mobility reductions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…These results align with earlier studies that reported a decrease in particulate matter during COVID-19 lockdowns (Conticini et al 2020;Tobias et al 2020;Wang et al 2020). However, studies on ozone and nitrogen dioxide yield mixed results, with some observing an increase in ozone during the lockdown period (Broomandi et al 2021;Tobias et al 2020), while others report a decrease (Conticini et al 2020;Wang et al 2020). These findings are consistent with prior research on air quality changes during COVID-19 lockdowns (Bao and Zhang, 2020).…”
Section: Figure 1 Significant Differences In Pollutants Concentration...mentioning
confidence: 99%
“…These results align with earlier studies that reported a decrease in particulate matter during COVID-19 lockdowns (Conticini et al 2020;Tobias et al 2020;Wang et al 2020). However, studies on ozone and nitrogen dioxide yield mixed results, with some observing an increase in ozone during the lockdown period (Broomandi et al 2021;Tobias et al 2020), while others report a decrease (Conticini et al 2020;Wang et al 2020). These findings are consistent with prior research on air quality changes during COVID-19 lockdowns (Bao and Zhang, 2020).…”
Section: Figure 1 Significant Differences In Pollutants Concentration...mentioning
confidence: 99%
“…There was a benefit, however, on wear and tear by the reduction in visitor volumes [27] and of air pollution which causes substantial deterioration on building materials such as stone, metal, glass and concrete [71]. Reduced air, land, and sea pollution, including 'human-generated sounds.…”
Section: Impact On Buildings and Collectionsmentioning
confidence: 99%
“….as a seismically detectable reduction in ground vibration' [25] (p. 267). In 24 cities studied around the world, there was significant reduction in pollutants (PM10, NO 2 , and SO 2 ) [71]. In Egypt, greenhouse gas emission reduced by 30-40% alongside reduction in air and water pollution ((Mostafa et al, 2021) in [72]).…”
Section: Impact On Buildings and Collectionsmentioning
confidence: 99%
“…Air quality worsens as people move from their residences to their destinations such as places of work, recreation centers, and grocery shops and becomes better as movement lessens. Indeed, air quality improved during COVID-19 lockdowns around the world (Sannigrahi et al 2021 ; Yechezkel et al 2021 ; Wijnands et al 2022 ; Naseer et al 2022 ; Benchrif et al 2021 ; Mishra et al 2021 ; Broomandi et al 2022 ; Arora et al 2020 ; Li et al 2022 ; Khan et al 2021 ; Nicolini et al 2022 ; Marinello et al 2021 ; Bar et al 2021 ), with most gains in air quality lost when the lockdowns were lifted, indicating that air quality could depict mobility patterns of individuals.…”
Section: Introductionmentioning
confidence: 99%